The role of self efficacy and adversity quotient in predicting basic mathematics competence within merdeka curriculum framework - Nurdin; Elzi Amilia Hasma; Mutmainna Ariska; Ma'rufi (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This research aims to determine whether these psychological factors serve as significant predictors of students’ performance in basic mathematics. Method: A quantitative correlational design was employed to assess the relationship between self-efficacy, AQ, and basic mathematical ability. Data were collected from 100 high school students using validated instruments that measured self efficacy, AQ, and mathematical competence. Descriptive and multiple regression analyses were conducted following the assumption tests for normality, linearity, and heteroscedasticity. Findings: The study found that self-efficacy significantly influences basic mathematics ability, whereas AQ did not show a significant partial effect. However, when combined, both self-efficacy and AQ exerted a joint influence on students’ mathematical performance. These findings suggest that psychological factors, in addition to cognitive and instructional elements, play an important role in developing mathematical competence. Significance: The study concludes that while strengthening conceptual understanding and structured learning support remains critical, integrating psychological competencies, such as self-efficacy and resilience, is essential to the success of the Merdeka Curriculum. This research underscores the need to foster both cognitive and psychological growth for effective student performance in mathematics.